Comparison of Hydrogen-Induced Oxide Charges Among GaN Metal-Oxide-Semiconductor Capacitors with Al2O3, HfO2, or Hf0.57Si0.43Ox Gate Dielectrics. (1st August 2022) - Irokawa, Yoshihiro; Inoue, Mari; Nabatame, Toshihide; Koide, Yasuo
Abstract : The effect of hydrogen on GaN metal-oxide-semiconductor (MOS) capacitors with Al2 O3, HfO2, or Hf0.57 Si0.43 O x gate dielectrics was studied using capacitance–voltage ( C–V ) measurements. Hydrogen exposure shifted all the C–V curves toward the negative bias direction, and the hydrogen response of the devices was reversible. When the hydrogen-containing ambient atmosphere was changed to N2, the C–V characteristics were found to gradually revert to the initial values in N2 . Application of a reverse gate bias accelerated the reversion compared with that in the absence of a bias, indicating that hydrogen was absorbed into the dielectric (Hf0.57 Si0.43 O x ) as positive mobile charges. This result is consistent with the direction of the shift of the C–V curves; positively charged hydrogen absorbed into a dielectric can cause a flatband voltage shift. The hydrogen-induced shift of the C–V curves varied depending on the dielectric. MOS devices with HfO2 -based high- k dielectrics were found to have approximately two to four times more incorporated charges than devices with Al2 O3 . Under the hypothesis that oxygen vacancies (VO s) trap hydrogen, the obtained results imply that the number of VO s in HfO2 -based high- k dielectrics is much larger than that in Al2 O3 -based dielectrics.